The Concordance between GeneXpert MTB/RIF and Isothermal Amplification Assay for Detecting Mycobacterium tuberculosis - Ulfah, Nuri Dzulfiani; Andriyoko, Basti; Turbawaty, Dewi Kartika (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Tuberculosis (TB) is an infectious disease and one of the biggest causes of death worldwide. The main problem today is the lack of accurate and rapid tests to detect Mycobacterium tuberculosis (MTB). Several molecular methods have been developed to detect MTB. GeneXpert MTB/RIF® can detect MTB and rifampicin resistance simultaneously in <2 hours. Cross Priming Amplification (CPA) is one of the isothermal amplification assay methods that can detect MTB. Both of these methods are molecular rapid tests so they can detect MTB faster. This study aims to evaluate the concordance of GeneXpert MTB/RIF® results with CPA to detect MTB at Hasan Sadikin General Hospital, Bandung. This is an observational cross-sectional study. The subjects were patients with suspected pulmonary TB and examined with GeneXpert MTB/RIF® then CPA (Ustar EasyNAT MTC™) was also examined. This study used total sampling with 50 subjects and analyzed with Cohen's Kappa test. The results of GeneXpert MTB/RIF® and Ustar EasyNAT MTC™ in detecting MTB obtained Kappa of 0.662 (good agreement) with p-value <0.001. Of the 11 low positive samples on GeneXpert MTB/RIF® as many as 6 subjects (54.55%) had positive results, and 5 subjects (45.45%) had negative results on UStar EasyNAT MTC™. Meanwhile, of the 4 very low positive samples, there was only 1 sample with positive results on UStar EasyNAT MTC™. There is a match results between high and medium positive GeneXpert MTB/RIF® and UStar EasyNAT MTC™. However, there is a difference between low and very low positive results on GeneXpert MTB/RIF® and UStar EasyNAT MTC™.